Jezabel rehúsa convertirse. Pero será castigada junto con sus hijos y sus amantes. Exégesis sobre Ap 2,21-22 - Caballero LC, José Antonio (Alpha Omega, 2012)
This article is a fourth one in a sequel of articles in the same magazine. It deals with the content of Rev 2: 21-22. Christ invites Jezabel of Thyatira to conversion at the risk of a severe punishment, being confined to a bed (her sin can turn against her and her children and lovers) in case she is still reluctant to convert. Her evil conduct has a limit in time.